ISSUES OF THE DEVELOPMENT OF FREELANCE ACTIVITY UNDER THE DEVELOPMENT OF THE DIGITAL ECONOMY - LUTPIDINOV, SHUXRAT (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the article, in the context of the ongoing COVID-19 pandemic in the world economy, each country is developing ways to sustainably develop the economy and ensure the employment of the existing population. It is aimed to develop freelance activities by opening a wide path to digital technologies and platforms in the economy.